Supertranslations and Superrotations at the Black Hole Horizon - Pino-Rozas, M (American Physical Society, 2016)
We show that the asymptotic symmetries close to nonextremal black hole horizons are generated by an extension of supertranslations. This group is generated by a semidirect sum of Virasoro and Abelian currents. The charges associated with the asymptotic Killing symmetries satisfy the same algebra. When considering the special case of a stationary black hole, the zero mode charges correspond to the angular momentum and the entropy at the horizon. © 2016 American Physical Society.